2011
DOI: 10.1016/j.jevs.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Approaches for the Assessment of Equine Chronic Pulmonary Disorders

Abstract: a b s t r a c tEven though the respiratory system is one of the most accessible organs for diagnostic testing, it is not always easy to define chronic lower airway disease in the horse. Diagnostic procedures performed by first opinion veterinarians in the field are often restricted to taking the history and performing clinical examination. Respiratory tract endoscopy, tracheal or bronchoalveolar lavage, and blood sampling are sometimes used but other specific ancillary examinations are seldom performed in stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…History, clinical exam, endoscopy of the respiratory tract, and cytology of the tracheal lavage are valuable tools for investigating respiratory disease [24]. In the current study, we observed that, among these, cytology of the tracheal lavage is the most effective method for diagnosis, for there were no changes on physical exam, clinical history, or even endoscopy that would justify the cytology profile observed in these animals.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…History, clinical exam, endoscopy of the respiratory tract, and cytology of the tracheal lavage are valuable tools for investigating respiratory disease [24]. In the current study, we observed that, among these, cytology of the tracheal lavage is the most effective method for diagnosis, for there were no changes on physical exam, clinical history, or even endoscopy that would justify the cytology profile observed in these animals.…”
Section: Discussionmentioning
confidence: 58%
“…Although endoscopy is an easily performed exam, it is still little used routinely. In a previous study with 100 horses, 22 underwent endoscopy, of which 20 had a tracheal sample collected for cytology [24]. Endoscopy is the only method capable of identifying functional disorders of the upper respiratory tract [36] [37].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to lung mechanics testing, endoscopic evaluation of the airways of horses presenting with respiratory disease is relatively commonplace in equine practice and is a principal diagnostic technique employed in the assessment of RAO cases. Visualisation of the tracheal lumen reveals an increase in tracheal mucus, a finding that has been shown to correlate with the presence of lower airway inflammation .…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%
“…An accurate characterization of the amount, location, and characteristics of pleural fluid or pleural thickening is easily obtained. Parenchymal lesions can be localized with high accuracy but often appear very similar and cannot be differentiated via an ultrasound examination [9]. During lung inflammation, the most common occurring artifact is comet tail, which can be detected in 91% of horses with equine asthma or exercise-induced pulmonary hemorrhage [10].…”
Section: Introductionmentioning
confidence: 99%